Collision-induced line parameters for the (2 ← 0) overtone band of HCl (1.76 µm) in binary mixtures with H2 and CH4. (September 2017) - Domanskaya, Alexandra V.; Li, Gang; Tran, Ha; Gisi, Michael; Ebert, Volker
Highlights: Experimental values for pressure broadening and shifts coefficients in the first overtone of HCl induced by hydrogen and methane. All results are novel. Results are of potential interest for biogas production and use. Abstract: We present experimental results on pressure broadening and shift coefficients in the first vibrational overtone band of HCl in gaseous mixtures with H2 and CH4 at room temperature. The whole set of collisional parameters for HCl–CH4 is novel. Most of the data for HCl–H2 system is also published for the first time. Our results have a precision of about 2% or better for shifts and below 1% for broadening in the band center.